The conjunction of Rationality and Mysticism in the Heart Sutra: An Epistemological Exploration - Djunatan, Stephanus (UIN Sunan Gunung Djati Bandung, 2023)
This study delves into the philosophical and epistemological interpretation of the Heart Sutra, emphasizing the conjunction between rational and mystical thought processes. The paper illustrates how the Sutra promotes an intertwined understanding of reality through textual analysis and comparative discussion involving Eastern and Western philosophical perspectives. The exploration reveals that the Heart Sutra serves as a profound guide, advocating for a balanced comprehension that integrates empirical rationality and mystical insight. The findings suggest that the notion of 'Shunyata' or emptiness encapsulates a complex relational understanding of being, where rational knowledge and mystical experiences are not only coexistent but mutually inclusive. This conjunctive approach challenges the conventional boundaries of epistemic thought and offers a comprehensive framework for understanding reality's multifaceted nature. This research contributes to the broader discourse on integrating traditional philosophical insights with contemporary epistemological frameworks, enriching both academic and practical understanding of spiritual texts.